Lagos Bat Virus Infection Dynamics in Free-Ranging Straw-Colored Fruit Bats (Eidolon helvum) - Suu-Ire, Richard; Fooks, Anthony; Banyard, Ashley; Selden, David; Amponsah-Mensah, Kofi; Riesle, Silke; Ziekah, Meyir; Ntiamoa-Baidu, Yaa; Wood, James; Cunningham, Andrew (Tropical medicine and infectious disease, 2017)
Bats are key species for ecological function, but they are also reservoirs of zoonotic agents, such as lyssaviruses that cause rabies. Little is known about the maintenance and transmission of lyssaviruses in bats, although the observation of clinically sick bats, both in experimental studies and wild bats, has at least demonstrated that lyssaviruses are capable of causing clinical disease in bat species. Despite this, extensive surveillance for diseased bats has not yielded lyssaviruses, whilst serological surveys demonstrate that bats must be exposed to lyssavirus without developing clinical disease. We hypothesize that there is endemic circulation of Lagos bat virus (LBV) in the straw-coloured fruit bat (Eidolon helvum) in Ghana, West Africa. To investigate this further, longitudinal blood sampling was undertaken quarterly between 2012 and 2014 on wild E. helvum at two sites in Ghana. Serum samples were collected and tested for LBV-neutralizing antibodies using a modified flourescent antibody virus neutralisation (FAVN) assay (n = 294) and brains from moribund or dead bats were tested for antigen and viral RNA (n = 55). Overall, 44.7% of the 304 bats sampled had LBV-neutralising antibodies. None of the brain samples from bats contained lyssavirus antigen or RNA. Together with the results of an earlier serological study, our findings demonstrate that LBV is endemic and circulates within E. helvum in Ghana even though the detection of viral infection in dead bats was unsuccessful. Confirmation that LBV infection is endemic in E. helvum in Ghana is an important finding and indicates that the potential public health threats from LBV warrant further investigation.